2015
DOI: 10.1371/journal.pone.0144726
|View full text |Cite
|
Sign up to set email alerts
|

Rhubarb Enema Attenuates Renal Tubulointerstitial Fibrosis in 5/6 Nephrectomized Rats by Alleviating Indoxyl Sulfate Overload

Abstract: AimTo investigate the effects of rhubarb enema treatment using a 5/6 nephrectomized rat model and study its mechanisms.MethodsTwenty-eight Sprague Dawley rats were divided into three groups: sham operation group (n = 8), 5/6 nephrectomized (5/6Nx) (n = 10), and 5/6Nx with rhubarb enema treatment (n = 10). The rhubarb enema was continuous for 1.0 month. Serum creatinine, serum indoxyl sulfate (IS) level, renal pathology, tubulointerstitial fibrosis, and renal oxidative stress were assessed.Results5/6Nx rats sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…33 Previous studies have indicated that Rhubarb has a promising protective effect against lung and renal fibrosis. 34,35 AE is an active compound in the plant rhubarb, 36 which is a traditional medicine used widely in the treatment of a variety of diseases in China. 37 Our study showed for the first time that AE protected against renal injury in a UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…33 Previous studies have indicated that Rhubarb has a promising protective effect against lung and renal fibrosis. 34,35 AE is an active compound in the plant rhubarb, 36 which is a traditional medicine used widely in the treatment of a variety of diseases in China. 37 Our study showed for the first time that AE protected against renal injury in a UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…Gubenxiezhuo is a mixture of Chinese medicine, including prepared rhubarb, monkshood, red ginseng, concha ostreae, carthamus tinctorious, and dandelion. The previous study has been documented that rhubarb decrease the renal tubulointerstitial in 5/6 neophrectomized rat via decreasing indoxyl sulfate overload (Lu, Zeng, Lu, Liu, & Zou, ). Red ginseng decreases pro‐inflammatory mediators in LPS‐treated macrophage to against endotoxic shock (Yayeh et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…In TCM, it has been considered that prepared rhubarb can clear heat away and discharge turbidity, and promote blood circulation and purging. One previous study indicated that prepared rhubarb inhibited renal tubulointerstitial fibrosis, and ameliorated renal oxidative stress and inflammatory injury [20]. When used in prescription in TCM, peach kernel can promote blood circulation and eliminate blood stasis.…”
Section: Discussionmentioning
confidence: 99%